A Systematic Review on Multidimensional Poverty Measurement - Putri, Anindya Mitra Raisnur; Shafiai, Muhammad Hakimi Mohd; Ismail , Abdul Ghafar (Journal of Ecohumanism, 2024)
Multidimensional poverty measurement (MPI) offers a more comprehensive framework for understanding poverty, as it includes various non-income dimensions such as education, health, and living standards. Traditional poverty measures, typically based on income thresholds, fail to capture the full spectrum of deprivation experienced by the poor. This systematic review examines key MPI methodologies, focusing on the widely used Alkire-Foster method and the Human Development Index, and explores how they are applied in different regional contexts. The review evaluates both the strengths and limitations of these approaches, including challenges related to indicator selection, weighting, and data availability. Furthermore, it discusses the policy implications of adopting MPI in national and global anti-poverty strategies, highlighting how MPI can offer policymakers more precise insights into the multidimensional nature of poverty. By synthesizing findings from recent empirical studies, this paper aims to contribute to the ongoing discourse on refining poverty measurement tools to better inform policy interventions and enhance poverty alleviation efforts globally. The review underscores the potential of MPI to address the shortcomings of unidimensional approaches and its importance in formulating more targeted, effective poverty reduction strategies.